2008
DOI: 10.1103/physrevlett.101.018301
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Mechanical Stability in Random Packings of Frictional Spheres

Abstract: Using sedimentation to obtain precisely controlled packings of noncohesive spheres, we find that the volume fraction RLP of the loosest mechanically stable packing is in an operational sense well defined by a limit process. This random loose packing volume fraction decreases with decreasing pressure p and increasing interparticle friction coefficient . Using x-ray tomography to correct for a container boundary effect that depends on particle size, we find for rough particles in the limit p ! 0 a new lower boun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 31 publications
9
158
1
Order By: Relevance
“…The length scale is L * = 2.55 m. which the definition of critical concentrations (such as the maximum random packing concentration) was more difficult. [29][30][31] When the solids fraction was in the 0.575-0.605 range, we observed three distinct regimes:…”
Section: A Regime Partitioningmentioning
confidence: 91%
“…The length scale is L * = 2.55 m. which the definition of critical concentrations (such as the maximum random packing concentration) was more difficult. [29][30][31] When the solids fraction was in the 0.575-0.605 range, we observed three distinct regimes:…”
Section: A Regime Partitioningmentioning
confidence: 91%
“…It was demonstrated that the random loose packing volume fraction decreases with increasing inter-particle friction coefficient 1,2 . The role of friction on force chains was investigated in reference 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, in [12] an average packing fraction of 0.55 is found for monodisperse spheres of diameter of the order of 100 μm and a packing fraction in the interval 0.50−0.55 for tetrahedrons and octahedrons [13].…”
Section: Validation Experimental Modelmentioning
confidence: 99%